2007
DOI: 10.1002/nag.612
|View full text |Cite
|
Sign up to set email alerts
|

Surface displacements due to batter piles driven in cross‐anisotropic media

Abstract: SUMMARYThis article derives the closed-form solutions for estimating the vertical surface displacements of crossanisotropic media due to various loading types of batter piles. The loading types include an embedded point load for an end-bearing pile, uniform skin friction, and linear variation of skin friction for a friction pile. The planes of cross-anisotropy are assumed to be parallel to the horizontal ground surface. The proposed solutions are never mentioned in literature and can be developed from Wang and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…He concluded that the ratio E/E for clays ranges from 0.6 to 4, and was as low as 0.2 for sands. However, for the heavily overconsolidated London clay, the range of E/E was 1.35-2.37, and that of the ratio G /E was 0.23-0.44 [Ward et al 1965;Gibson 1974;Lee and Rowe 1989;Tarn and Lu 1991;Wang et al 2008]. The ratio ν/ν is hypothetically assumed to be within the range 0.75-1.5 in this study.…”
Section: An Illustrative Examplementioning
confidence: 80%
“…He concluded that the ratio E/E for clays ranges from 0.6 to 4, and was as low as 0.2 for sands. However, for the heavily overconsolidated London clay, the range of E/E was 1.35-2.37, and that of the ratio G /E was 0.23-0.44 [Ward et al 1965;Gibson 1974;Lee and Rowe 1989;Tarn and Lu 1991;Wang et al 2008]. The ratio ν/ν is hypothetically assumed to be within the range 0.75-1.5 in this study.…”
Section: An Illustrative Examplementioning
confidence: 80%
“…He concluded that the ratio E/E for clays ranges from 0.6 to 4, and was as low as 0.2 for sands. However, for the heavily overconsolidated London clay, the range of E/E was 1.35-2.37, and that of the ratio G /E was 0.23-0.44 [Ward et al 1965;Gibson 1974;Lee and Rowe 1989;Tarn and Lu 1991;Wang et al 2008]. The ratio ν/ν is hypothetically assumed to be within the range 0.75-1.5 in this study.…”
Section: An Illustrative Examplementioning
confidence: 83%
“…The present vertical stress solutions as well as the surface displacement solutions [14] could offer practical engineers a complete and useful reference when piles are driven in an isotropic/crossanisotropic earth mass. Furthermore, a parametric analysis demonstrates that the vertical stresses with the consideration of pile batter are considerably different from those calculated from plumb piles.…”
Section: Discussionmentioning
confidence: 99%